Microglial positron emission tomography (PET) imaging in epilepsy: Applications, opportunities and pitfalls. (January 2017) - Scott, Gregory; Mahmud, Mohammad; Owen, David R.; Johnson, Michael R.
Abstract: Neuroinflammation is increasingly implicated in epileptogenesis and epilepsy. Microglia are an important mediator of central nervous system inflammation, and the development of positron emission tomography (PET) radioligands which bind the Translocator Protein (TSPO), an outer mitochondrial membrane protein expressed by microglia, has enabled in vivo measurement of neuroinflammation. Here, we outline the principles and potential pitfalls of TSPO PET imaging in relation to epilepsy, and opportunities for using TSPO imaging as a biomarker for future anti-inflammatory based therapeutics in epilepsy.